2020
DOI: 10.3389/fimmu.2020.591803
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between NLRP3 Inflammasome and Autophagy

Abstract: The NLRP3 inflammasome is cytosolic multi-protein complex that induces inflammation and pyroptotic cell death in response to both pathogen (PAMPs) and endogenous activators (DAMPs). Recognition of PAMPs or DAMPs leads to formation of the inflammasome complex, which results in activation of caspase-1, followed by cleavage and release of pro-inflammatory cytokines. Excessive activation of NLRP3 inflammasome can contribute to development of inflammatory diseases and cancer. Autophagy is vital intracellular proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
259
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(271 citation statements)
references
References 159 publications
(231 reference statements)
11
259
1
Order By: Relevance
“…Inflammasomes regulate and interact with various RCDs ( 72 , 76 78 ). The inhibitors of either Nlrp3 inflammasome/pyroptosis (inhibitor OLT1177) or NETosis (inhibitor GSK484) can suppress to each other ( Figure 4 ), suggests there could exist a cross-talk between these 2 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes regulate and interact with various RCDs ( 72 , 76 78 ). The inhibitors of either Nlrp3 inflammasome/pyroptosis (inhibitor OLT1177) or NETosis (inhibitor GSK484) can suppress to each other ( Figure 4 ), suggests there could exist a cross-talk between these 2 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies highlight interactions between autophagy and the NLRP3 inflammasome (Biasizzo and Kopitar-Jerala, 2020 ); while the specific role of the P2X 7 receptor is usually not involved, autophagic degradation of inflammasome components is predicted to regulate the ability of the P2X 7 receptor to activate the NLRP3 inflammasome. Increased autophagy is associated with decreased NLRP3 inflammasome function in vivo in rodent microglial cells (Chen et al, 2019 ), and in primary microglia cells (Cho et al, 2014 ; Chen et al, 2019 ; Han et al, 2019 ).…”
Section: Effect Of Priming and Autophagy On P2x 7 mentioning
confidence: 99%
“…Numerous studies showed that autophagy is a negative regulator that prevents excessive activation of inflammasomes (Biasizzo and Kopitar-Jerala, 2020; Deretic et al, 2013; Harris et al, 2017; Krakauer, 2019; Netea-Maier et al, 2015; Qian et al, 2017). We therefore speculated that OMV-dependent inhibition of autophagic flux could exacerbate inflammasome activation.…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that these OMVs inhibit the autophagic flux and are much more prone to overactivate the non-canonical inflammasome pathway, the main host defense mechanism against infections that must be tightly regulated to ensure a correct antimicrobial response. Autophagy is one of the main negative regulator of inflammasome activation and plays a protective role in inflammatory diseases such as sepsis (Biasizzo and Kopitar-Jerala, 2020; Feng et al, 2019; Ho et al, 2016; Qiu et al, 2019). Thus, these OMVs, produced by bacteria responsible of extraintestinal infections, could destabilize the host response to the infection, thus facilitating its progression.…”
Section: Introductionmentioning
confidence: 99%